The Demand for Electricity and Natural Gas in the Northeastern United States - Beierlein, James G.; Dunn, James W.; McConnon, James C. (The Review of Economics and Statistics, 1981)
James G. Beierlein, James W. Dunn, James C. McConnon, Jr., The Demand for Electricity and Natural Gas in the Northeastern United States, The Review of Economics and Statistics, Vol. 63, No. 3 (Aug., 1981), pp. 403-408